IMPLEMENTATION OF PROVIDING LEGAL AID FOR UNDERPRIVILEGED DETAINEES IN CLASS 1 STATE DETENTION CENTER, CENTRAL JAKARTA - Sulton Zaki Ananda; Umar Anwar (Polteknik Ilmu Pemasyarakatan, 2021)
Every prisoner in the detention center has the right to get legal assistance. Legal aid is given to everyone, including underprivileged prisoners. However, at the Class 1 detention center in Central Jakarta, not all detainees receive free legal aid from the state. The problem formulation used by the author is 1) How is the provision of legal aid for the poor as suspects and defendants to be able to get legal assistance at the Class 1 Rutan Central Jakarta? 2) What are the obstacles faced by the suspect and the defendant in obtaining legal aid rights for the poor as suspects and defendants at the Class 1 Rutan Central Jakarta? The research objectives in this paper are 1) To be able to find out the provision of legal aid for underprivileged prisoners. 2) To find out what are the obstacles that occur in providing legal aid at the Class 1 Rutan Central Jakarta and what are the obstacles faced by the defendant and suspect in obtaining legal aid services for poor prisoners at the Class 1 Rutan Central Jakarta. This study uses empirical juridical research methods, namely research conducted on the actual situation or real conditions that have occurred in the community with the intention of knowing and finding the facts and data needed, based on the results of data analysis conducted at the Class I Rutan Central Jakarta related to the implementation of assistance. The law for prisoners is not able to explain that 1) The process of providing legal aid to poor prisoners to obtain legal aid services begins with the legal counseling process to the legal assistance and legal consultation process. 2) The legal aid process at the Central Jakarta Class 1 Rutan has not been running optimally and there are still obstacles in its implementation. In terms of their rights as suspects and defendants, they have the right to obtain this legal aid service, especially for those who are unable to use the services of an advocate. But in the field, what happens is the opposite, there are still differences in treatment in the fulfillment of this right. For this reason, it is very necessary to know the realization of legal aid for prisoners belonging to low economic class in Central Jakarta Class 1 Rutan. The conclusions from the results of the research are that 1) The provision of legal assistance in the Class 1 Rutan Central Jakarta begins with a legal counseling process. 2) There are several obstacles, namely, the lack of confidence of prisoners in the legal aid program and there are still many detainees who do not know what legal aid is and what rights they get. Setiap tahanan yang ada di Rutan memiliki hak untuk mendapatkan bantuan hukum. Bantuan hukum diberikan kepada setiap orang termasuk tahanan yang kurang mampu. Tetapi,di Rutan kelas 1 Jakarta Pusat tidak semua tahanan mendapatkan bantuan hukum secara Cuma Cuma pada negara. Rumusan masalah yang digunakan penulis adalah 1) Bagaimana pemberian bantuan hukum untuk terhadap rakyat miskin sebagai tersangka dan terdakwa untuk bisa mendapatkan bantuan hukum di Rutan Klas 1 Jakarta Pusat ? 2) Apa saja hambatan yang dihadapi tersangka dan terdakwa dalam mendapatkan hak bantuan hukum terhadap rakyat miskin sebagai tersangka dan terdakwa di Rutan Klas 1 Jakarta Pusat ? Tujuan penelitian dalam penulisan ini adalah 1) Untuk dapat mengetahui pemberian bantuan hukum bagi Tahanan kurang mampu. 2) Untuk mengetahui hambatan apa saja yang terjadi dalam pemberian bantuan hukum di Rutan Klas 1 Jakarta Pusat dan apa saja hambatan yang dihadapi oleh terdakwa dan tersangka dalam mendapatkan layanan bantuan hukum bagi tahanan miskin di Rutan Klas 1 Jakarta Pusat. Penelitian ini menggunakan metode penelitian yuridis emipiris yaitu penelitian yang dilakukan terhadap keadaan nyata yang telah terjadi di masyarakat dengan maksud untuk mengetahui dan menemukan fakta fakta dan data yang dibutuhkan, berdasarkan hasil analisis data yang dilakukan di Rutan Klas I Jakarta Pusat terkait pelaksanaan bantuan hukum bagi tahanan tidak mampu menjelaskan bahwa 1) Proses pemberian bantuan hukum untuk tahanan miskin untuk mendapatkan layanan bantuan hukum diawali dengan proses penyuluhan hukum sampai proses pendampingan hukum dan konsultasi hukum. 2) Proses bantuan hukum di Rutan Klas 1 Jakarta Pusat belum berjalan maksimal dan masih ditemui kendala-kendala dalam pelaksanaannya. Dalam hal hak sebagai tersangka maupun terdakwa mereka mempunyai hak untuk mendapatkan layanan bantuan hukum ini, terutama bagi mereka yang tidak sanggup menggunakan jasa advokat. Namun di lapangan adalah sebaliknya, masih terjadi perbedaan perlakuan dalam pemenuhan hak ini. Untuk itu sangat perlu untuk diketahuinya realisasi bantuan hukum bagi tahanan yang tergolong ekonomi rendah di Rutan Klas 1 Jakarta Pusat. Kesimpulan dari hasil penelitian bahwa 1) Pemberian bantuan hukum di Rutan Kelas 1 Jakarta Pusat diawali dengan proses penyuluhan hukum. 2) Terdapat beberapa hambatan yaitu, kurangnya rasa percaya tahanan terhadap program bantuan hukum dan masih banyak dari tahanan yang tidak mengetahui apa itu bantuan hukum dan hak yang mereka peroleh.